Kindergarten and elementary school teachers’ numeracy knowledge and understanding - Farida, Alief; Agung Ginanjar Anjaniputra; Sri Wuli Fitriati; Issy Yuliasri; Pasca Kalisa (Acitya: Journal of Teaching and Education, 2025)
Numeracy is essential for students to achieve academic success and develop practical problem-solving abilities in their daily lives. This study aims to investigate the integration of numeracy into the teaching practices of different lessons by elementary school and kindergarten teachers in Semarang, Indonesia. The data of this qualitative research were acquired from 26 teachers using a qualitative technique, which involved an open-ended questionnaire and the analysis of lesson plans. The result of the study shows that only two of the four components of numeracy were known by the teachers. Domain I, which pertains to quantitative information, is the most prominent. Still, Domain II, which relates to spatial information, and Domain IV, which encompasses strategies, techniques, and tools, are noticeably lacking. The study emphasizes the need to provide well-rounded teacher training that covers all aspects of numeracy in order to improve the quality of numeracy instruction. The implications indicate the need for specific professional development programs to solve these gaps, thereby enhancing students’ numeracy skills and academic achievement. Keywords: application of numeracy components, elementary education, numeracy